L’expérience de la vulnérabilité comme ressource politique : une approche phénoménologique - Mickaëlle Provost (Genre, Sexualité et Société)
The aim of this paper is to understand vulnerability as a lived experience through the lens of phenomenology. First, this approach helps to think about the ambivalence of vulnerability by questioning the passivity which can be attached to it. Vulnerability can, on the contrary, be seen as a capacity to be affected or as an exposure to what is not predictable. This ambivalence of vulnerability can however be atrophied in specific political and social situations (sexism, colonialism and racism), rendering vulnerability mostly negative. The challenge is then to understand how these different dimensions of vulnerability are intertwined in terms of lived experience and how to work on vulnerability, how it can be modified and oriented in the perspective of ethical and political resistance.